Analisis Kualitas Pelayanan Publik Pada Dinas Kependudukan Dan Catatan Sipil Kabupaten Dompu - Jibril Alwi Jahir; Indah Ariffianti; I Nengah Arsana (Kredibel: Jurnal Ilmiah Manajemen, 2024)
This study aims to determine the quality of public services at the Population and Civil Registry Office of Dompu Regency. This research method is descriptive research using a qualitative approach. The collection technique used observation, interviews, and documentation of research informants determined using purposive sampling and snowball sampling techniques. The informants in this study were the head of the population and civil registration office of Dompu district and 4 community users as supporting informants. The data analysis procedure used has several stages, namely, data collection, data reduction, data presentation, and verification. The results of this study indicate that the quality of public services at the Population and Civil Registry Office of Dompu Regency is assessed from the dimensions of physical evidence classified as incomplete, good ability reliability, excellent responsiveness, assurance does not provide clarity, empathy applies a good attitude. The conclusion of this study is that the quality of public services at the Population and Civil Registration Office of Dompu Regency has sufficiently met some of the expectations of the people of Dompu.